ANALISIS TINGKAT KEPUASAN KLIEN TERHADAP PELAYANAN KESEHATAN DI PUSKESMAS DALAM WILAYAH KOTA PADANG TAHUN 2006 - Nizwardi Azkha; Deni Elnovriza (Faculty of Public Health, Andalas University, 2007)
To win emulation, Health Centre have to be able give satisfaction to all client. A Health Centre successful, the client is a goal and capital which must be defended by its existence. The Quality of Health Services more related at officer comments dimension in fulfilling requirement of patient. The Aim of research is to know describe the patient satisfaction to health services at Health Centre in Padang Regency in 2006. Design of research is qualitative descriptive. Population in this research is the client who come to health centre in Padang Regency, with the amount of sample is 400 people. Primary data in collecting by direct interview to responder by use questioner instrument, Secondary data taking away from Health Centre and Health Office in Padang. Analysis data done with univariat analysis, Importance and Performance analysis and it’s processing by manual and computerize. The result of research found that most responder express important to give service, attribute found on priority kwadran A is health officer quickly listen carefully, action quickly at the time of client require, officer quickly listen carefully to sign of client, polite and friendly officer service and officer give special attention. to client. Importance Performance between Priority and satisfaction around 76,84% - 83,96%, Where attribute owning storey 80% have been told to satisfy, while attribute which is storey more than 80% expressed by less satisfied where the attribute is timely service schedule, officer health quickly listen carefully in handling sigh of client, action quickly at the time of client require, officer quickly listen carefully to sigh of client, polite and friendly officer service and officer give special attention to client.For that have to be more pay attention things lionized by responder, have to be more improve employees discipline to on schedule in fulfilling health service, and room freshment, and also look after equipment, readiness and hygiene of appliance in giving health service.